Is Rumenteng Siang the future of public space performing arts in West Java? - Ganang Dwi Asmoro (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2021)
Performing arts venues are one of the public spaces essential to developing the human spirit. Almost all performing arts buildings in Indonesia are old Dutch heritage. One of the public spaces for performing arts in the city of Bandung is the Rumenteng Siang building. This place was previously the old building of the former Rivoli Cinema, which was later used as an arts performance space. This research uses a descriptive qualitative method, which discusses the facilities and existence of this public space. The result of this research is the discovery that Rumenteng Siang has experienced a decline in the number of viewers. One of the leading causes is the lack of quality art performances presented in the building. Apart from that, the lack of adequate facilities for art presenters is also an obstacle. Inadequate facilities can reduce the performance quality and the audience's interest in attending the event. Not only that, the lack of comfortable facilities for visitors also reduces the existence of this public space. Therefore, efforts are needed to improve facilities and the quality of performing arts presented at Rumenteng Siang. It can be done through collaboration between management, government, and the arts community to improve facilities and present quality arts performances. In this way, it is hoped that Rumenteng Siang can maintain its existence as an essential public space in developing the human spirit through art